Rancang Bangun Aplikasi Digital Marketing Berbasis Web Menggunakan CodeIgniter Untuk Meningkatkan Omzet Penjual di Pasar Ciroyom - Khoerunisa, Asti; Supriyati, S; Natansya, Tyas Sylva Fitrian; Nissa, Rika Sovyatun; Fernaldy, Kevin; Bahri, Ramadhan Syaeful (Labkat Press KA FTIK UNIKOM, 2023)
Expired goods are the condition of a product that is no longer suitable for consumption or use because it has a high risk of causing poisoning for people who consume it or use it. For sellers, especially in traditional markets, there is no way or system to be able to inform goods that are approaching expiration and are still fit for sale, so it can result in goods that are approaching expiration simply being thrown away. The purpose of this study is to develop a digital marketing application design for frozen preparations that are almost expiring to increase trader turnover in the Ciroyom market. The research method used is experimental and descriptive research methods. The system development methodology used is Waterfall. The results of this study explain that digital marketing applications of near-expired frozen processed products in the Ciroyom market have been analyzed by existing sales procedures, which we then developed to overcome the emerging drawbacks of near-expired product sales. This digital marketing application can overcome some of the problems with selling frozen preparations that are about to expire. This digital marketing application can sell merchandise that is almost expired online so consumers can see what items are available.